Leaf isoprene and monoterpene emission distribution across hyperdominant tree genera in the Amazon basin - Jardine, Kolby J.; Zorzanelli, Raquel F.; Gimenez, Bruno Oliva; Oliveira Piva, Luani Rosa de; Teixeira, Andrea; Fontes, Clarissa Gouveia; Robles, Emily; Higuchi, Niro; Chambers, Jeffrey Quintin; Martin, Scot T. (Phytochemistry, 2020)
Tropical forests are acknowledged to be the largest global source of isoprene (C5H8) and monoterpenes (C10H16) emissions, with current synthesis studies suggesting few tropical species emit isoprenoids (20–38%) and do so with highly variable emission capacities, including within the same genera. This apparent lack of a clear phylogenetic thread has created difficulties both in linking isoprenoid function with evolution and for the development of accurate biosphere-atmosphere models. Here, we present a systematic emission study of “hyperdominant” tree species in the Amazon Basin. Across 162 individuals, distributed among 25 botanical families and 113 species, isoprenoid emissions were widespread among both early and late successional species (isoprene: 61.9% of the species; monoterpenes: 15.0%; both isoprene and monoterpenes: 9.7%). The hyperdominant species (69) across the top five most abundant genera, which make up about 50% of all individuals in the Basin, had a similar abundance of isoprenoid emitters (isoprene: 63.8%; monoterpenes: 17.4%; both 11.6%). Among the abundant genera, only Pouteria had a low frequency of isoprene emitting species (15.8% of 19 species). In contrast, Protium, Licania, Inga, and Eschweilera were rich in isoprene emitting species (83.3% of 12 species, 61.1% of 18 species, 100% of 8 species, and 100% of 12 species, respectively). Light response curves of individuals in each of the five genera showed light-dependent, photosynthesis-linked emission rates of isoprene and monoterpenes. Importantly, in every genus, we observed species with light-dependent isoprene emissions together with monoterpenes including β-ocimene. These observations support the emerging view of the evolution of isoprene synthases from β-ocimene synthases. Our results have important implications for understanding isoprenoid function-evolution relationships and the development of more accurate Earth System Models. © 2020 Elsevier Ltd